INTELLECTUAL CAPITAL EFFICIENCY AND FINANCIAL PERFORMANCE OF LISTED MANUFACTURING FIRMS IN NIGERIA (Journal of Global Accounting, 2024)
The study examined the effect of intellectual capital efficiency on financial performance of listed manufacturing firms in Nigeria. The specific objective was to examine the effect of human capital efficiency, structural capital efficiency, relational capital efficiency and capital employed efficiency on net assets per share. Ex-post facto research design was adopted in the study. The study population comprised 64 manufacturing firms listed under consumer goods sector, industrial goods sector, oil and gas sector, ICT sector, healthcare sector and conglomerate sector of Nigerian Exchange Group. However, purposive sampling was used in selecting a sample size of 55. Secondary data for the study were sourced from the firms annual reports for a period of nine years (2015-2023).The hypotheses were tested using Panel Estimated Generalized Least Squares. The findings revealed that: human capital efficiency has a significant positive effect on Net Assets Per Share of listed manufacturing firms in Nigeria (p-value = 0.0002); structural capital efficiency has a significant positive effect on Net Assets Per Share of listed manufacturing firms in Nigeria (p-value = 0.0012); relational capital efficiency has a significant positive effect on Net Assets Per Share of listed manufacturing firms in Nigeria (p-value = 0.0015); capital employed efficiency has a non-significant positive effect on Net Assets Per Share of listed manufacturing firms in Nigeria (p-value = 0.7257). In conclusion, investing in human capital, optimizing structural processes, nurturing external relationships, and efficiently utilizing financial resources enable manufacturing firms in Nigeria to achieve sustainable growth and improved financial metrics. Therefore, the study recommends among others that Human Resource Managers should invest in continuous training and development programs for employees to enhance their skills and competencies in order to improve individual performance but also drive overall organizational productivity, thereby increasing Net Assets Per Share.
Keywords: Capital Employed Efficiency; Financial Performance; Intellectual Capital Efficiency; Net Assets Per Share; Structural Capital Efficiency